Ransom my heart eaudiobook A novel. - Cabot, Meg (Tantor Media, 2020)
Mia Thermopolis, Princess of Genovia and star of Meg Cabot's insanely popular #1 New York Times bestselling Princess Diaries books, has "penned" her first historical romance novel . . . with help from Meg Cabot. He's a tall, handsome knight with a secret. She's an adventurous beauty with more than a few secrets of her own. Finnula needs money for her sister's dowry, and fast. Hugo Fitzstephen, returning home to England from the Crusades with saddlebags of jewels, has money, and lots of it. What could be simpler than to kidnap him and hold him for ransom? Well, for starters, Finnula could make the terrible mistake of falling in love with her hostage.